Efforts to Prevent Double Voter Data on Election Fairness - Sitanggang, Putri Adila; Sinaga, Budiman (Golden Ratio of Data in Summary, 2025)
In a democratic system, regional head elections (Pilkada) are essential pillars of electing leaders and representatives of the people. However, inaccurate voter data in the integrity of elections often causes problems in implementing elections, including double data. Double data not only undermines the principle of fairness but can potentially reduce public trust in democracy. Therefore, election monitoring is essential to maintain the fairness and openness of the voting process. People's constitutional rights are affected by this issue, as they need assistance to report changes in voter data or match unregistered data. According to the election monitoring results, almost all communities in Medan have conducted matching and research (cockpit) properly. However, the issue of double data is still a problem that Bawaslu must monitor again. The author collects information about the 2024 Pilkada from the Election Supervisory Board of Medan City. There is still double data in the community. This research aims to determine how well the cockpit works to avoid double data and how it affects voting and fairness. This research shows that most citizens of Medan City have followed the procedures when conducting cockpit, thus reducing the possibility of double data. Transparency, public trust, and community engagement in the elections also increased. In addition, this monitoring activity also provides suggestions for improving the double data prevention system, including increasing cooperation between election organizers and independent monitors, expanding cockpit socialization to the community, and using artificial intelligence-based technology for automatic detection. Such measures ensure integrity, fairness, and transparency in elections.